Healthy planet, healthy people: Nature-positive contributions to food and nutrition security in Viet Nam - Boukaka, Sedi Anne; Azzarri, Carlo; Davis, Kristin E.; Dao, The Anh; Vu, Dang Toan (International Food Policy Research Institute, 2024)
The Asia-Pacific region houses 52% of the world's 767.9 million undernourished people. Although the prevalence of undernourishment in Viet Nam nearly halved from 2000 to 2019, progress slowed due to climate change, conflict, and other factors. Some 5.1 million people, or 5.2% of the population in Viet Nam are undernourished (FAO 2021). In rural areas, particularly among ethnic groups, these rates are higher. For instance, household food insecurity in rural districts in the Vietnamese Mekong Delta prevalence was 34.4% and 48.4% in the last month and last year, respectively. The rates of stunting and underweight among children aged under five in ethnic groups in Viet Nam remain at 31.4% and 21% respectively, according to the National Institute of Nutrition (2023).